Foreign aid and economic growth of the South Pacific microstates : selected case studies of the Cook Islands, Kiribati, Samoa and the Solomon Islands (1970-1995) : a research thesis submitted in fulfilment of the requirements for the degree of Masters of Applied Economics at Massey University - Viviani, Ron (Massey University, 1999)
The purpose of foreign aid has traditionally been to assist developing countries to progress through the transition period from economic stagnation to self-sustaining economic growth. For most island economies foreign aid is a key factor in their economic growth and development. It provides a source for foreign exchange, fills the investment-savings gap and meets the shortfall in resource needs. This study presents an empirical analysis of the relationship between foreign aid and economic growth for the South Pacific Microstates (SPMs) of the Cook Islands, Kiribati, Samoa, and the Solomon Islands. A neoclassical production function is employed to evaluate the aid-growth nexus. The Auto-Regressive Distributed Lag (ARDL) method to cointergration regression is applied to time series data for the period 1970 to 1995 for each of the selected case studies. The various components of foreign aid such as bilateral, multilateral, grant, loan, and technical co-operation aid are utilised to evaluate the disaggregated effects of foreign aid on economic growth. Other determinants of growth such as investment, domestic savings, government consumption and exports are also included in this analysis. Empirical evidence indicates that foreign aid and its various components i.e. bilateral, multilateral, loan, grant, and technical co-operation aid, has not contributed positively or significantly to the Cook Islands and Kiribati's economic growth. The poor performance of government authorities in these South Pacific Microstates is the best explanation for such an outcome. The results for the larger SPMs of Samoa and the Solomon Islands show positive aid-growth relationships. As such, bilateral, grant, and loan aid contributes to economic growth for Samoa. In the case of the Solomon Islands the results are more interesting with various components of foreign aid having a stronger influence on economic growth than the aggregated form of foreign aid. That is, the impact of bilateral, grant, and technical co-operation aid on economic growth is positive and significant in the long-run. As for other determinants of economic growth it is apparent that exports is the only factor that significantly contributes to the economic performance of all these SPMs. Government consumption and the labour force has been productive for Samoa, however, the Cook Islands, Kiribati and the Solomon Islands display negative or insignificant results for these variables. Investment provides strong support for the economic growth of both Samoa and the Solomon Islands, however, in the case of the later it is a short term impact. Domestic savings in these two SPMs are well below investment levels and do not contribute to their country's growth performance. Overall, it is seen that domestic resources (i.e. exports) have a stronger influence on the economic performance of the Cook Islands and Kiribati compared to foreign resources (i.e foreign aid). However, with limited growth of the domestic resources in these SPMs it is difficult to maintain sustained economic growth while relying on exports only. The challenge for the Cook Islands and Kiribati is to improve the productiveness of foreign resources and reduce large and inefficient government sectors. As for Samoa and the Solomon Islands the performance of domestic resources contributes more to the economies of these countries than foreign resources. Moreover, foreign resources also contribute to economic growth. For Samoa and the Solomon Islands to benefit and sustain economic growth and development, it is important to implement policies that encourage private sector development and also have a stable economic environment.
Keywords: Economic assistance; Economic conditions; Oceania; Cook Islands; Kiribati; Solomon Islands